2010
DOI: 10.1021/ja101524z
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Reveals the Hydrophobic-Core Location of Poly(amidoamine) Dendrimers in Biomembranes

Abstract: Poly(amidoamine) (PAMAM) dendrimer nanobiotechnology shows great promise in targeted drug delivery and gene therapy. Because of the involvement of cell membrane lipids with the pharmacological activity of dendrimer nanomedicines, the interactions between dendrimers and lipids are of particular relevance to the pharmaceutical applications of dendrimers. In this study, solid-state NMR was used to obtain a molecular image of the complex of generation 5 PAMAM dendrimer with the lipid bilayer. Using 1H radio freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 64 publications
3
91
0
Order By: Relevance
“…Supported lipid bilayers (SLBs) are well suited for studying the dendrimer-membrane interactions, as they lend themselves readily to quantitative analysis using a range of surface sensitive techniques such as X-ray and neutron reflectivity (XRR and NR) [14,80,81], atomic force microscopy (AFM) [82][83][84], ellipsometry [14,85], quartz crystal microbalance with dissipation (QCM-D) [81,85,86], NMR [87], differential scanning calorimetry (DSC) and Raman spectroscopy [88].…”
Section: Interactions Between Pamam Dendrimers With Supported Lipid Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Supported lipid bilayers (SLBs) are well suited for studying the dendrimer-membrane interactions, as they lend themselves readily to quantitative analysis using a range of surface sensitive techniques such as X-ray and neutron reflectivity (XRR and NR) [14,80,81], atomic force microscopy (AFM) [82][83][84], ellipsometry [14,85], quartz crystal microbalance with dissipation (QCM-D) [81,85,86], NMR [87], differential scanning calorimetry (DSC) and Raman spectroscopy [88].…”
Section: Interactions Between Pamam Dendrimers With Supported Lipid Bmentioning
confidence: 99%
“…Cell membranes modulate their lipid phase behaviour by varying their composition. This results in different crystalline lipid phases, important for membrane fusion [92][93][94] and the formation of lipid rafts (microdomains of one lipid type) [95], conjectured to regulate membrane signalling and cellular entry [87]. The molecular packing and thus the bilayer structure can be tuned by using different lipids to mimic different membranes [83].…”
Section: Interactions Between Pamam Dendrimers With Supported Lipid Bmentioning
confidence: 99%
See 1 more Smart Citation
“…21,59 Investigations of the interaction between cationic dendrimers and artificial and cellular lipid bilayers revealed electrochemical as well as hydrophobic interactions that promote membrane disruption and impair transport mechanisms. 70,71 The formation of pores in the outer mitochondrial membrane promotes apoptotic cell death. 72 In our experiments, the localization of native and bioconjugate dendrimers in the mitochondria correlated well with International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 54.191.190.102 on 13-May-2018 For personal use only.…”
Section: Pamam and Bc-pamam Localization Within Mitochondriamentioning
confidence: 99%
“…Smith and coworkers investigated the effect of G5 and G7 PAMAM dendrimers on multilamellar vesicles by solid-state NMR techniques. They have found that dendrimers have higher impact on alkyl chain region than on headgroups; besides they used partially hydrated or highly concentrated, fully hydrated membranes [37].…”
Section: Introductionmentioning
confidence: 99%